One Man, Two Names: A Case of Onomastic Strategies at the Beginning of the 19ᵗʰ Dynasty - Serrano Delgado, José Miguel (Mitteilungen des Deutschen Archäologischen Instituts Kairo, 2024)
In the area around the tomb of Djehuty (TT 11), a unique set of shabtis with two different names, Tutuia and Nebmehyt, has been found. This paper offers an in-depth study of both onomastic forms, understanding that one is dealing with a case of double names. The name Tutuia, despite a certain ambiguity and polyvalence, can be of foreign origin, possibly Semitic. Nebmehyt is instead typically Egyptian but may involve a metaphorical reference to Egypt’s neighbouring peoples and countries from the north. The fact that both names were held by the same person could be interesting data that has to do with the image and integration of foreigners in the early Ramesside Period. This research aims to be a case study and contribution to understanding onomastic strategies and the role of double names in Egyptian society.